2014
DOI: 10.1039/c4ra06215a
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology of electrospun PLA fibers: mechanisms of pore formation

Abstract: Interaction of relative humidity with solvent(s) is relatively more important in obtaining surface pores than solvent volatility and phase separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…It can be inferred from the aforementioned discussion that VIPS leads to the creation of micro/nano roughness. These findings are similar to the recent works by Lu and Xia and Natarajan et al …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It can be inferred from the aforementioned discussion that VIPS leads to the creation of micro/nano roughness. These findings are similar to the recent works by Lu and Xia and Natarajan et al …”
Section: Resultssupporting
confidence: 93%
“…It can be inferred from the aforementioned discussion that VIPS leads to the creation of micro/nano roughness. These findings are similar to the recent works by Lu and Xia 50 and Natarajan et al 51 It is worth mentioning that Figure 7 schematically shows the mechanism of pore formation and does not necessarily emphasize the shape of pores, or even the size and number of vapor molecules.…”
Section: The Mechanism Of the Roughness Formation On Fiber Surface Ansupporting
confidence: 90%
“…A combination of solvent and non-solvent (or poor solvent) has also been used to induce porosity in PLA fibres. When studying a ternary system composed of PLA/DCM/DMF, Natarajan and co-workers [37] found that the addition of DMF (10 % v/v) resulted in surface porosity. Similar systems have been used to produce porous PLA fibres by Li et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the electrospinning process, the environment of jet volatilization is relatively dry. 23,[27][28][29] Chloroform mixed with chloroform ethanol is used as a solvent. Ethanol is a volatile nonsolvent for PLA.…”
Section: Preparation Of Microspheresmentioning
confidence: 99%